Perbedaan jumlah mikronukleus mukosa gingiva dan mukosa bukal akibat radiasi radiografi panoramik - Mufida Dzuriyatin Syarifah; Rini Widyaningrum; Rurie Ratna Shantiningsih (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2020)
Objectives: Panoramic radiography exposure causes DNA damage and micronucleus formation. The gingival mucosa and buccal mucosa were used to identify the number of micronucleus due to radiation exposure because they have a high prevalence of oral cancer in Southeast Asia. This research is aimed to determine the difference between micronucleus formation at the buccal mucosa and the gingival mucosa after exposed by conventional panoramic radiography in the Dentomaxillofacial Radiology Installation of Prof. Soedomo dental hospital, Universitas Gadjah Mada. Material and Methods: Samples were obtained by rolling the cervical brush against the buccal and gingival mucosa at 10 days after radiation exposure. Samples were stained using the Feulgen-Rossenbeck method and analyzed under binuclear light microscope with a 400x magnification. Results: Analysis of independent T tests showed that there was a significant difference (p<0,05) in the increasing of micronucleus formation between the buccal mucosa and the gingival mucosa. The average difference in the number of micronucleus were 5,5/1000 cells. Conclusion: There were differences in the increasing of micronucleus between the buccal mucosa and the gingival mucosa due to exposure of conventional panoramic radiography. The buccal mucosa had higher increase than the gingival mucosa.